The chloroplast genome of black pepper (Piper nigrum L.) and its comparative analysis with related Piper species - Gaikwad, Ambika Baldev; Kaila, Tanvi; Maurya, Avantika; Kumari, Ratna; Rangan, Parimalan; Wankhede, Dhammaprakash Pandhari; Bhat, K. V. (Frontiers in Plant Science, 2023)
Piper nigrum, also known as black pepper, is an economically and ecologically important crop of the genus Piper. It has been titled as the king of spices due to its wide consumption throughout the world. In the present investigation, the chloroplast genome of P. nigrum has been assembled from a whole genome sequence by integrating the short and long reads generated through Illumina and PacBio platforms, respectively. The chloroplast genome was observed to be 161,522 bp in size, having a quadripartite structure with a large single copy (LSC) region of 89,153 bp and a small single copy (SSC) region of 18,255 bp separated by a copy of inverted repeats (IRs), each 27,057 bp in length. Taking into consideration all the duplicated genes, a total of 131 genes were observed, which included 81 protein-coding genes, 37 tRNAs, 4 rRNAs, and 1 pseudogene. Individually, the LSC region consisted of 83 genes, the SSC region had 13 genes, and 18 genes were present in each IR region. Additionally, 216 SSRs were detected and 11 of these were validated through amplification in 12 species of Piper. The features of the chloroplast genome have been compared with those of the genus Piper. Our results provide useful insights into evolutionary and molecular studies of black pepper which will contribute to its further genetic improvement and breeding.